2015
DOI: 10.1123/ijsnem.2013-0107
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Modification Decreases Arterial Stiffness in Overweight and Obese Men: Dietary Modification vs. Exercise Training

Abstract: Obesity and increased arterial stiffness are independent risk factors for cardiovascular disease. Arterial stiffness is increased in obese individuals than in age-matched nonobese individuals. We demonstrated that dietary modification and exercise training are effective in reducing arterial stiffness in obese persons. However, the differences in the effect on arterial stiffness between dietary modification and exercise training are unknown. The purpose of the current study was to compare the effect of dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Our study also found that essential hypertension had different effects on bone mineral density at different sites. The mechanism may be that ① different parts of body differ in skeletal muscle strength and exhibit inconsistent activity, which leads to varied effects on bone mineral density at different sites [ 38 – 40 ]. Ward's triangle is primarily composed of cancellous bone, has a local blood supply that is poor, and is prone to fracture; therefore, Ward's triangle is a sensitive region for detecting bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that essential hypertension had different effects on bone mineral density at different sites. The mechanism may be that ① different parts of body differ in skeletal muscle strength and exhibit inconsistent activity, which leads to varied effects on bone mineral density at different sites [ 38 – 40 ]. Ward's triangle is primarily composed of cancellous bone, has a local blood supply that is poor, and is prone to fracture; therefore, Ward's triangle is a sensitive region for detecting bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important for obese individuals to commit to losing weight before developing such diseases. We previously reported that lifestyle modification, consisting of dietary modification and habitual aerobic exercise training, is effective for weight loss and lowering the risk of cardiovascular diseases in obese individuals 7) .…”
Section: Introductionmentioning
confidence: 99%
“…CAVI changes over a short period of time in response to alterations in circulatory conditions; it is sensitive to subclinical changes in major arteries before impairment and it can be a reliable indicator of treatment effectiveness or modification in lifestyle [ 34 ]. Healthy lifestyle, physical exercise and smoking cessation, for example, prevent and treat early vascular aging [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%